ADAPTING AND TRANSFORMING ELT DURING AND POST COVID-19 ERA: PEOPLE, PLACES, AND PURPOSES - O’Boyle, Aisling Marie; Samanhudi, Udi (TEFLIN Journal, 2023)
This article discusses the adaptations and possible transformations in ELT during and post COVID-19 times. The traditional focus for ELT is often a narrow perspective on teaching methodology, epitomized by the “3 Ps” in ELT- Present, Practice, Produce. We argue for a realignment of focus to “People, Places, and Purposes” in ELT and a focus on addressing social issues. We frame our discussion on the notion of being ultra-social and illustrate the creativity and adaptability in language use during the pandemic. Questioning the deeply held assumptions in ELT, we propose transformative action on social issues: speaking, shifting boundaries and sustainability.